Financial Performance Analysis of Regional Governments: A Study of South Sumatra Province in 2019–2023 - Maryani Ayunda; Nurhasanah Rizki; Choiruddin Choiruddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the financial performance of regional governments in South Sumatra Province from 2019 to 2023. The research uses the ratio analysis technique based on the Regional Revenue and Expenditure Budget (APBD), focusing on five key indicators: regional financial independence, effectiveness, efficiency, harmony, and growth. This quantitative descriptive study collects secondary data from the official reports published by the Audit Board of Indonesia (BPK) and the Ministry of Finance. The results show that the level of regional financial independence in South Sumatra is still low and dependent on central government transfers. The effectiveness and efficiency ratios vary among districts/cities but tend to improve over the years. The harmony ratio indicates that the allocation to operational expenditure remains dominant, while capital expenditure is still relatively limited. Meanwhile, the growth ratio shows positive but inconsistent trends across regions. These findings suggest that regional governments should strengthen their revenue-generating capacity, optimize budget allocation, and prioritize capital investment to enhance regional financial performance and autonomy.